STRATEGI KOMUNIKASI SOSIALISASI KPU KOTA BLITAR DALAM MENINGKATKAN PARTISIPASI PEMILIH PEMULA PADA PILKADA TAHUN 2024 - Akmal, Daffa; Haryanti, Nik; Reta, Anita (Prodi Ilmu Komunikasi Universitas Sahid Surakarta, 2026)
The Blitar City General Election Commission (KPU) is an independent institution established to carry out its duties as the organizer of general elections including regional head elections. The KPU plays a crucial role in organizing transparent and fair elections. First-time voters are those exercising their right to vote for the first time. This study was conducted using qualitative methods with a participatory observation approach to determine the communication strategies implemented by the Blitar City KPU to increase first-time voter participation in the 2024 regional head elections. The research was motivated by the still suboptimal public involvement in the regional head elections, especially among first-time voters, based on an evaluation of previous elections. The results of the study indicated that the strategies used by the Blitar City KPU include face-to-face outreach to senior high schools and universities, organizing activities segmented by first-time voters, and utilizing social media. The results of the study provided input regarding specific communication strategies to attract the interest of first-time voters to exercise their right to vote for the first time in political life.